Impact of 18F-PSMA-1007 uptake in prostate cancer using different peptide concentrations: preclinical PET/CT study on mice - Soeda, Fumihiko; Watabe, Tadashi; Naka, Sadahiro; Liu, Yuwei; Horitsugi, Genki; Neels, Oliver C.; Kopka, Klaus; Tatsumi, Mitsuaki; Shimosegawa, Eku; Giesel, Frederik L.; Hatazawa, Jun (Journal of nuclear medicine, 2019)
PET radioligands with low molar activity (MA) may underestimate the quantity of the target of interest because of competitive binding of the target with unlabeled ligand. The aim of this study was to evaluate the change in the whole-body distribution of 18F-PSMA-1007 targeting prostate-specific membrane antigen (PSMA) when solutions with different peptide concentrations are used. Methods: Mouse xenograft models of LNCaP (PSMA-positive prostate cancer) (n = 18) were prepared and divided into 3 groups according to the peptide concentration injected: a high-MA group (1,013 ± 146 GBq/μmol; n = 6), a medium-MA group (100.7 ± 23.1 GBq/μmol; n = 6), and a low-MA group (10.80 ± 2.84 GBq/μmol; n = 6). Static PET scans were performed 1 h after injection (scan duration, 10 min). SUVmean in tumor and normal organs was compared by the multiple-comparison test. Immunohistochemical staining and Western blot analysis were performed to confirm expression of PSMA in tumor, salivary gland, and kidney. Results: The low-MA group (SUVmean, 1.12 ± 0.30) showed significantly lower uptake of 18F-PSMA-1007 in tumor than did the high-MA group (1.97 ± 0.77) and the medium-MA group (1.81 ± 0.57). On the other hand, in salivary gland, both the low-MA group (SUVmean, 0.24 ± 0.04) and the medium-MA group (0.57 ± 0.08) showed significantly lower uptake than the high MA group (1.27 ± 0.28). The tumor-to-salivary gland SUVmean ratio was 1.73 ± 0.55 in the high-MA group, 3.16 ± 0.86 in the medium-MA group, and 4.78 ± 1.29 in the low-MA group. The immunohistochemical staining and Western blot analysis revealed significant overexpression of PSMA in tumor and low expression in salivary gland and kidney. Conclusion: A decrease in the MA level of the injected 18F-PSMA-1007 solution resulted in decreased uptake in tumor and, to a greater degree, in normal salivary gland. Thus, there is a possibility of minimizing the adverse effects in salivary gland by setting an appropriate MA level in PSMA-targeting therapy.